High-pressure behaviors of carbon nanotubes - Zhao, Z.S.; Zhou, X.-F.; Hu, M.; Yu, D.L.; He, J.; Wang, H.-T.; Tian, Y.J.; Xu, B. (Сверхтвердые материалы, 2012)
In this paper, we have reviewed the experimental and theoretical studies on pressure-induced polygonization, ovalization, racetrack–shape deformation, and polymerization of carbon nanotubes (CNTs). The corresponding electronic, optical, and mechanical changes accompanying these behaviors have been discussed. The transformations of armchair (n, n) CNT bundles (n = 2, 3, 4, 6, and 8) under hydrostatic or nonhydrostatic pressure into new carbons, including recently proposed superhard bct-C₄, Cco-C₈, and B-B1AL2R2 carbon phases have also been demonstrated. Given the diversity of CNTs from various chiralities, diameters, and arrangements, pressure-induced CNT polymerization provides a promising approach to produce numerous novel metastable carbons exhibiting unique electronic, optical, and mechanical characteristics. Розглянуто експериментальні та теоретичні дослідження з індукованою тиском полігонізації, овалізації, деформації у формі бігової доріжки і полімеризації вуглецевих нанотрубок (ВНТ). Обговорено відповідні електронні, оптичні і механічні зміни, що супроводжують ці процеси. Також продемонстровано перетворення в ВНТ у формі крісла (n, n), зібраних в пучок (n = 2, 3, 4, 6 і 8) під гідростатичним або негідростатичним тиском в нові вуглецеві алотропи, в тому числі недавно запропоновані надтверді bct-C₄, Cco-C₈ і B-B1AL2R2-вуглецеві фази. Різноманітність ВНТ з різними хіральністю, діаметрами та упаковками, а також полімеризація ВНТ, викликана тиском, забезпечує перспективний підхід для отримання численних нових метастабільних вуглецевих фаз, що демонструють унікальні електронні, оптичні і механічні характеристики. Рассмотрены экспериментальные и теоретические исследования по индуцированной давлением полигонизации, овализации, деформации в форме беговой дорожки и полимеризации углеродных нанотрубок (УНТ). Обсуждены соответствующие электронные, оптические и механические изменения, сопровождающие эти процессы. Также продемонстрированы преобразования в УНТ в форме кресла (n, n), собранных в пучок (n = 2, 3, 4, 6 и 8) под гидростатическим или негидростатическим давлением в новые углеродные аллотропы, в том числе недавно предложенные сверхтвердые bct-C₄, Cco-C₈ и B-B1AL2R2-углеродные фазы. Разнообразие УНТ с различными хиральностью, диаметрами и упаковками, а также полимеризация УНТ, вызванная давлением, обеспечивает перспективный подход для получения многочисленных новых метастабильных углеродных фаз, демонстрирующих уникальные электронные, оптические и механические характеристики.